Finite Element Analysis and optimization design of sprinkler Truss Structure. Issue 1 (1st November 2022) - Wang, Changhu; Meng, Weiyun; Wang, Jianxiang; Min, Xiangmei
Abstract: This paper includes three sections. Truss structures have been widely applied in bridges and buildings due to their light weight, reasonable load-bearing, and high material utilization rate. For truss structures serving as load-bearing carriers, their structural strength should be guaranteed, and moreover, their economic performance should be considered. First, the finite element theory was introduced, and the computer-aided simulation analysis was performed by combining numerical analysis and finite element theory. Second, the truss structure of a sprinkler was subjected to a mechanical analysis, and its stability was explored with its maximum displacement and maximum stress as constraints. Finally, the truss structure was optimally designed until its stability, strength, and stiffness met relevant requirements.